As origens da informatização do lar brasileiro: o caso do computador doméstico (1984-1986) - Bueno, Silvia Helena de Araujo [UNIFESP] (2015)
When the writing of history leans towards new objects, new methods and new problems; leading historians to log out raids on land that has not sufficiently explored, especially regarding the examination of the general problems of the contemporary extreme. The realization that the contemporary world is home to a largely technological society is nothing new. This new reality is that the process of current human and social transformation is directly linked to these technologies. In this sense it is essential to highlight the potential of computer technology for personal use as field of interest of historiography. Thus, this research is meant to identify the possible sources of computerization of the Brazilian home, with the personal computer privileged object of analysis. Delimited in the panorama of the years 1984-86, a period that gives the ambience of household computers and related commercial activities, the study assumes that the creation of desire for consumption was an important agent for the dissemination of the computer equipment market, and advertising materials constructed to the product prime source of analysis. Rises as hypothesis that the development of computer technology in Brazil comes from conditioning factors as the automation of the home environment, the centrality of life within the home and the rise of a youth culture created in the vicinity of computer equipment